2023
DOI: 10.1186/s40337-023-00733-y
|View full text |Cite
|
Sign up to set email alerts
|

Asian students in the anglosphere – unravelling the unique familial pressures contributing to eating pathology: a systematic review

Abstract: Background There is no clear consensus on the specific familial pressures affecting Asian students in the Anglosphere, despite the validation of the Tripartite Influence model of eating disturbances in this group. However, traditional familial risk factors for disordered eating can be elevated for immigrant Asians with collectivistic-oriented familial dynamics, necessitating an examination of the culture-specific risk profile for eating pathology in student-aged Asians. This systematic review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Future research should aim to investigate the generalizability of our findings across diverse temporal and geographical contexts. Last but not least, a recent systematic review indicated that Asian adolescents may develop maladaptive behaviors as compensatory mechanisms for the unremitting psychological distress generated from overprotection of family environment under the influence of traditional filial piety (Sun et al, 2023). NSSI could be compensatory behaviors under over protecting environment and further research need to fully decipher the link between NSSI and traditional filial piety in Chinese culture.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Future research should aim to investigate the generalizability of our findings across diverse temporal and geographical contexts. Last but not least, a recent systematic review indicated that Asian adolescents may develop maladaptive behaviors as compensatory mechanisms for the unremitting psychological distress generated from overprotection of family environment under the influence of traditional filial piety (Sun et al, 2023). NSSI could be compensatory behaviors under over protecting environment and further research need to fully decipher the link between NSSI and traditional filial piety in Chinese culture.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%